Revival of classic Affixes in Spanish through English - Isabel De La Cruz-Cabanillas; Cristina Tejedor Martinez (Moderna Språk)
The increasing impact of English upon Spanish pervades not only its lexicon, but also its morphology. The goal of the article is to see if the revival of several affixes in Spanish is likely due to English influence. These affixes, available in the classic languages, have mainly come down to us through Latin, even though some of them are Greek in origin. This article focuses on the revival of several of these classic affixes that are highly productive in Present-Day Spanish. The data have been retrieved from a corpus containing twenty-first-century written texts in European Spanish and have been compared to information from other corpora and several lexicographic works both in English and Spanish. The resources that are mentioned enable the chronological order of the recording of the items to be traced. This timeline will help to establish the influence of the English lexical units in the coinage of their Spanish counterparts.